COMPUTATIONAL FLUID DYNAMIC (CFD) SIMULATION OF SLUG FLOW WITHIN PIPE BEND AND PIPE ELBOW WHICH INDUCE VIBRATION - MOHAMED KHAIRI, MOHAMED IKRAM (IRC, 2020)
Multi-phase flow is any fluid stream consisting of more than one phase or component, for example, gas-liquid stream, liquid-liquid flow, solid fluid stream, or solid-fluid gas stream. It is common in fluid systems, in particular in oil and gas hydrocarbon conveying systems which produce natural gas and crude oil at the same time. A significant response from flux-induced vibration can lead to potential fatigue damage or uncontrolled vibration when the frequency of excitation matches the piping system's natural frequencies, especially in cases where oil produces dense sand particles or slow flows in the flow-lines. This is why it is important to investigate the impact of the oil-gas-water mix on pipeline structure.